Out of control?: acting out anger is associated with deficient prefrontal emotional action control in male patients with borderline personality disorder - Bertsch, Katja; Krauch, Marlene; Cackowski, Sylvia; Herpertz, Sabine (Neuropharmacology, 2019)
Difficulty in anger control and anger-related aggressive outbursts against others are frequently reported by patients with borderline personality